Production of subtilisin proteases in bacteria and yeast - A. S. Rozanov; S. V. Shekhovtsov; N. V. Bogacheva; E. G. Pershina; A. V. Ryapolova; D. S. Bytyak; S. E. Peltek (Вавиловский журнал генетики и селекции)
In this review, we discuss the progress in the study and modif ication of subtilisin proteases. Despite longstanding applications of microbial proteases and a large number of research papers, the search for new protease genes, the construction of producer strains, and the development of methods for their practical application are still relevant and important, judging by the number of citations of the research articles on proteases and their microbial producers. This enzyme class represents the largest share of the industrial production of proteins worldwide. This situation can explain the high level of interest in these enzymes and points to the high importance of designing domestic technologies for their manufacture. The review covers subtilisin classif ication, the history of their discovery, and subsequent research on the optimization of their properties. An overview of the classes of subtilisin proteases and related enzymes is provided too. There is a discussion about the problems with the search for (and selection of) subtilases from natural strains of various microorganisms, approaches to (and specifics of) their modif ication, as well as the relevant genetic engineering techniques. Details are provided on the methods for expression optimization of industrial subtilases of various strains: the details of the most important parameters of cultivation, i. e., composition of the media, culture duration, and the inf luence of temperature and pH. Also presented are the results of the latest studies on cultivation techniques: submerged and solid-state fermentation. From the literature data reviewed, we can conclude that native enzymes (i. e., those obtained from natural sources) currently hardly have any practical applications because of the decisive advantages of the enzymes modified by genetic engineering and having better properties: e. g., thermal stability, general resistance to detergents and specif ic resistance to various oxidants, high activity in various temperature ranges, independence from metal ions, and stability in the absence of calcium. The vast majority of subtilisin proteases are expressed in producer strains belonging to different species of the genus Bacillus. Meanwhile, there is an effort to adapt the expression of these enzymes to other microbes, in particular species of the yeast Pichia pastoris.